Regional Integration and Food Security in West Africa: Challenges, Opportunities and Sustainable Solutions - Muhammad, Abdulrasheed; Babatunde, Ahmed Yusuf (Hasanuddin Journal of International Affairs, 2024)
Regional integration and food security are pivotal aspects of sustainable development, especially in the context of West Africa. The Economic Community of West African States (ECOWAS) represents one of the regional arrangements on political cooperation and economic integration in Africa. While regional integration holds the promise of bolstering food security through collective efforts, its success in fostering food security has encountered a myriad of challenges in West Africa. This study analyzed the problems and potential opportunities of regional integration in West Africa. From the analysis, it became evident that the ECOWAS faces unique challenges and opportunities as it strives to achieve a balance between economic collaboration and ensuring an adequate stable food supply for its growing population. Some of the problems of regional integration in West Africa include trade barriers, lack of unified agricultural policy, border issues and environmental problems. Notwithstanding these problems, collaboration within the ECOWAS framework presents avenues for member countries to unlock economic potential, foster stability, and collectively address food security challenges. It is therefore recommended that the ECOWAS needs to adopt a common agricultural policy, implement water management strategies, develop various market information systems and embark on different capacity building programmes in order to ensure food security among ECOWAS countries.